PEMERIKSAAN CRYPTOCOCCAL ANTIGEN ANTARA METODE SISTEM AGLUTINASI LATEKS ANTIGEN KRIPTOKOKUS DAN LATERAL FLOW ASSAY DI PASIEN AIDS (Cryptococcal Antigen of Acquired Immune Deficiency Syndrome with Lateral Flow Assay and Cryptococcus Antigen Latex Agglutination System) - Artiti Aditya; Indrati AR; Ganiem AR (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2014)
Cryptococcosis is the fourth most common opportunistic infection among Acquired Immune Deficiency Syndrome (AIDS) patients.About 100% mortality has been reported within two weeks in patient with cryptococcal meningitis but without specific treatment. Theaim of the study was to compare Cryptococcal antigen (CrAg) detection between Cryptococcus Antigen Latex Agglutination System(CALAS) and Lateral Flow Assay (LFA) among AIDS patients. This research was designed as comparative analytic with cross sectionalstudy on 56 serum derived from AIDS patient who visited Teratai Clinic before ARV therapy initiation and who had never been diagnosedas Cryptococcal meningitis. Each sample was tested for CrAg with CALAS and LFA according to the manufacturer instructions. Thisstudy was conducted in the Clinical Pathology Laboratory at Dr. Hasan Sadikin Hospital/Centre Research Unit (CRU) Medical Faculty,Padjajaran University between December 2012March2013. The statistical analysis was done using Chi square test. The result showed thatthere was no significant difference between CALAS and LFA method with p=0.596 (p>0.05), the positive probability of CrAg detectionusing LFA was 0.75 times compared to the CALAS method. For the CrAg detection in the AIDS patients there was no significant differencebetween CALAS and LFA and the positive probability of CrAg for LFA was detected about 0.75 times compared to the CALAS method.